High Lyso-Gb3 Plasma Levels Associated with Decreased miR-29 and miR-200 Urinary Excretion in Young Non-Albuminuric Male Patient with Classic Fabry Disease. (10th January 2019) - Jaurretche, Sebastián; Perez, Germán R.; Venera, Graciela
Abstract : Renal involvement is associated with a greater morbidity and mortality in Fabry disease. Pathological albuminuria, the first Fabry nephropathy clinical manifestation, can occur from early childhood, although histological lesions such as tubulo-interstitial fibrosis and glomerulosclerosis are present or may precede the onset of pathological albuminuria. In renal cells, exposure to Lyso-Gb3 is correlated with increased expression of Transforming Growth Factor- β eta (TGF- β ). miR-21, miR-192, and miR-433 that promote fibrosis are activated by TGF- β, and miR-29 and miR-200 that suppress fibrosis are inhibited by TGF- β . A 23-year-old male was diagnosed with FD. α GalA decreased enzyme activity: 0.1 nmol/hour/liter; genotype: [c.317T>G (p.L106R)]; GFR: 104.4 mL/min/m 2 ; urinary albumin excretion: 6.00 mg/day; plasma Lyso-Gb3: 124.5 nmol/L. A decrease urinary excretion of miR-29 and miR-200 was found (p <0.005) compared to controls. In addition to its usefulness as a phenotype marker, Lyso-Gb3 has been proposed as an indicator of therapeutic response. We detect an association of high Lyso-Gb3 plasma values with decreased urinary excretion of miRNAs with known antifibrotic effect (miR-29 and miR-200). Although the present work is a case report, it could be hypothesized that one of the harmful Lyso-Gb3 effects could be the miRNAs regulation through changes in TGF- β expression.